Analisis Yuridis Keabsahan Smart Contract Sebagai Bentuk Perjanjian Elektronik di Indonesia - Rifka Lolyana Oktavia Sitorus; Restu Putri Nilakandi; Aurillia Silmi Ayu Khoirunnisa; Rayi Kharisma Najib (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The development of blockchain technology has encouraged the use of smart contracts as a form of automated agreements in digital transactions in Indonesia. However, the absence of specific regulations regarding their validity has raised doubts regarding the fulfillment of agreement elements and legal certainty. This article aims to analyze the validity of smart contracts as electronic agreements by reviewing their compliance with the requirements for valid agreements in the Civil Code and the provisions of the Electronic Information and Transactions Law. This study uses a normative juridical method with a regulatory and conceptual approach to identify the legal basis and limitations of smart contract implementation. The findings of this study indicate that smart contracts can be declared valid as electronic agreements as long as they fulfill the elements of agreement, competence, clear object, and lawful cause, and are executed through a reliable and accountable electronic system. However, there are still gaps in the regulations regarding the mechanism of evidence, the responsibilities of the parties, and the resolution of code-based disputes that are automatic in nature. The implications of this research emphasize the need to strengthen regulations and technical guidelines to provide legal certainty and encourage the use of smart contracts in digital transactions in Indonesia.